2012
DOI: 10.1111/j.1524-475x.2012.00867.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of combined radiation and burn injury on the renin–angiotensin system

Abstract: The renin angiotensin system (RAS) plays an important role in wound repair; however, little is known pertaining to RAS expression in response to thermal and the combination of radiation plus burn injury (CRBI). The purpose of this study was to test the hypothesis that thermal injury modifies expression of RAS components and CRBI delayed this up-regulation of RAS. Skin from uninjured mice was compared to mice receiving local thermal injury or CRBI (injury site). Skin was analyzed for gene and protein expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 51 publications
0
18
0
Order By: Relevance
“…Of the two widely studied AngII receptors, AT1-receptor is characterized as the primary regulator for AngII mediated dermal fibrosis. In one study on the effects of thermal skin injury on the Renin-Angiotensin-System in a murine model, the data indicated that AT1-receptor expression was increased in the fibroblasts of injured mice but absent in the fibroblasts of unwounded skin [23]. Similarly, AT1-receptor, as compared to AT2-receptor, was found to be more prominently expressed in the dermis of wounded rats [24].…”
Section: Discussionmentioning
confidence: 99%
“…Of the two widely studied AngII receptors, AT1-receptor is characterized as the primary regulator for AngII mediated dermal fibrosis. In one study on the effects of thermal skin injury on the Renin-Angiotensin-System in a murine model, the data indicated that AT1-receptor expression was increased in the fibroblasts of injured mice but absent in the fibroblasts of unwounded skin [23]. Similarly, AT1-receptor, as compared to AT2-receptor, was found to be more prominently expressed in the dermis of wounded rats [24].…”
Section: Discussionmentioning
confidence: 99%
“…With injury, expression of the receptor for NorLeu 3 -A(1-7), Mas, increases in skin. The cellular components with upregulated expression include cells of the hair follicle, hyperplastic epidermis and dermis [18]. Unpublished studies using microarray technology show that a cassette of genes is upregulated in granulation tissue of wounds treated with NorLeu 3 -A(1-7) (compare first lane from the right [G-P; granulation-placebo] with the fourth lane from the right [G-N; granulation-NorLeu 3 -A(1-7)].…”
Section: Drug Summary Boxmentioning
confidence: 99%
“…In human skin, AT 1 and AT 2 receptors were found in the epidermis and in dermal vessel walls [8]. Recently, an upregulation of the Mas receptor, the functional receptor for A(1-7), in the skin after injury has been shown [18] (Figure 2). The same expression pattern was found for angiotensinogen, the parent protein, renin and angiotensin converting enzyme (ACE).…”
Section: Introduction To Norleu3-a(1-7)mentioning
confidence: 99%
“…15 Recently, an upregulation of the Mas receptor, the functional receptor for A(1-7), in the skin after injury has been shown. 25 Once the activity of A(1-7) was identified, a series of analogs were generated and tested for activity in both in vitro and in vivo models of healing. In these studies, NorLeu3-A(1-7) was found to be most active in the acceleration of wound repair and had the novel mechanism of restoration of skin architecture, for example, regeneration.…”
Section: Renin-angiotensin System In Dermal Tissuementioning
confidence: 99%